25th Anniversary Article: Hybrid Nanostructures Based on Two‐Dimensional Nanomaterials. (10th March 2014) - Huang, Xiao; Tan, Chaoliang; Yin, Zongyou; Zhang, Hua
<x xml:space="preserve">Abstract</x> Two‐dimensional (2D) nanomaterials, such as graphene and transition metal dichalcogenides (TMDs), receive a lot of attention, because of their intriguing properties and wide applications in catalysis, energy‐storage devices, electronics, optoelectronics, and so on. To further enhance the performance of their application, these 2D nanomaterials are hybridized with other functional nanostructures. In this review, the latest studies of 2D nanomaterial‐based hybrid nanostructures are discussed, focusing on their preparation methods, properties, and applications.